2018
DOI: 10.1055/s-0038-1636543
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 and Survival in Peripheral Artery Disease Patients

Abstract: Survival of peripheral arterial disease (PAD) patients increased over the last decade due to increased use of secondary preventive medication and rapid revascularization of PAD patients. Angiogenetic markers such as vascular endothelial growth factor (VEGF), angiopoietin-2 (Ang-2) and its receptor Tie-2 might be useful markers to assess the residual risk for mortality in PAD patients. The aim of this study was to evaluate angiogenetic markers for the prediction of mortality in a PAD cohort. For this purpose, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additionally, other angiogenic markers such as VEGF or angiopoetin-2, a marker known to be associated with increased mortality in PAD patients, 30 were not associated with angiogenin levels. No association of angiogenin and VEGF has been reported in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, other angiogenic markers such as VEGF or angiopoetin-2, a marker known to be associated with increased mortality in PAD patients, 30 were not associated with angiogenin levels. No association of angiogenin and VEGF has been reported in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 90%
“…Fasting blood samples were collected at study entry and stored at À80 C. Plasma angiogenin levels were measured using a sandwich enzyme-linked immunosorbent assay (ELISA; R&D Systems Inc) with an intra-assay and inter-assay variation of 4.7% and 8.4%, respectively. Angiopoietin-2, Tie-2, and VEGF have been already assessed in this patient cohort 30 using bead-based multiplex assay for the Luminex platform with a sensitivity of 17.1, 16.0, and 2.1 pg/mL (R&D Systems). The intra-assay and inter-assay coefficient of variation for angiopoietin-2, Tie-2, and VEGF levels were 5.7 and 3.2%, 7.0 and 3.6%, and 9.7 and 5.0%, respectively.…”
Section: Sample Collection and Measurement Of Angiogenetic Proteinsmentioning
confidence: 99%
“…Angpt2, an angiogenetic marker, was found to be associated with destabilized endothelial cell junctions and enlarged lumen formation [ 28 ]. Angpt2 was considered as a proangiogenic factor that could be responsible for endothelial dysfunction and increased risk for vascular disorders [ 29 ] and functioned as a biomarker to predict the life expectancy of peripheral arterial disease patients [ 30 ]. A multi-center case–control study on stroke patients further showed the association of variants in the promoter of Angpt2 with stroke [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large community‐based study [25], higher ANGPT2 concentrations were associated with a greater risk of all‐cause and cardiovascular mortality in a general population during a median follow‐up time of 6.2 years. ANGPT2 also predicted all‐cause mortality in two clinical studies including high‐risk patient populations, one of which consisted of subjects with peripheral arterial disease [26] and one with chronic kidney disease [27]. In other smaller clinical studies of very high‐risk populations, including patients with AMI complicated with cardiogenic shock [19, 20] and acute decompensated HF [17], ANGPT2 was also found to be an independent predictor of all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%